Evaluation of Triple Integrals with Continuous Integrands Numerically by Using Method RM(RMM) - Mahdi Muosa AL-Gasas, Safaa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The main aim of this paper is to evaluate triple integrals with continuous integrands numerically by using extension resulting from best methods that find the approximate values of single integral Romberg acceleration with Mid-point rule (RM) on the exterior dimension Z with one of methods that find the approximate values for the double integral and it Romberg acceleration with Mid-point rule on both dimensions of interior X and middle Y, (RMM) when the number of divisions on the interior dimension is equal to the number divisions on the middle dimension , but both is not equal to the number divisions on the exterior dimension and we shall call this method by RM(RMM), where we got high accuracy in the results by few subintervals relatively and few time.